Microbial quality and antioxidant activity of an improved bitter gourd (Momordica charantia L.) drink - Chern, Pei Ern (2017)
The bitter gourd (Momordica charantia L.) (MC) is being consumed in various countries due to its nutritional value and is high in antioxidants. In this study, the (MC) is used in the preparation of a ready-to-serve (RTS) drink with antioxidant properties. The objectives of this research are to determine the physicochemical and antioxidant properties of a RTS MC drink with different concentrations of the MC, to conduct a sensory evaluation on the MC drink for acceptability and finally to determine the effect of water quality of the MC drink stored at different temperatures. The MC drink was prepared by water extraction of its juice, added with dissolved brown sugar, artificial honey, low fat yogurt, lime juice and mint extract. A proximate analysis was carried out followed by DPPH radical scavenging assay. A sensory evaluation was then carried out among 40 untrained panelists on a Hedonic scale of 1 to 7. The microbial quality was determined using the aerobic plate count, enumeration of moulds and yeasts, presumptive test for coliforms and detection of Escherichia coli. Five concentrations (0.58, 0.70, 0.80, 0.90 and 1.00 g/mL) of the MC drink was developed. The proximate analyses carried out showed that the RTS drink consist of high moisture content from 92.94 – 94.65%. The pH and ˚Brix of the MC drink increased as the concentration increased, whereby the pH was 4.30 – 4.54, and the ˚Brix was 5.0 – 5.6. The increase in concentration of MC has led to an increase in the radical scavenging activity. At the original concentration of 0.58 g/mL, the inhibition was at 71.51% which increased to 87.22% at the final concentration of 1.00 g/mL. The most accepted concentration of the MC drink according to the sensory evaluation was 0.80 g/mL with a mean score of 4.09 (like slightly), while the least accepted concentration was 1.00 g/mL and obtained the lowest mean score of 3.80 (dislike slightly). At the selected concentration (0.80 g/mL), the amount of bacterial growth exceeded 6 log CFU/mL after 24 hours for the MC drink stored at room temperature (28±2˚C). When stored at refrigerated temperature (4±2˚C) it took 72 hours to reach 6 log CFU/mL. The total coliform count for all juice samples were between 93-210 MPN/g. E. coli was detected in the MC drink but not in the water used for its preparation. This study demonstrated MC has the potential to be used as an ingredient in preparing RTS drinks containing antioxidant properties.